2009
DOI: 10.1523/jneurosci.4643-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

GABA Transporter-1 Activity Modulates Hippocampal Theta Oscillation and Theta Burst Stimulation-Induced Long-Term Potentiation

Abstract: The network oscillation and synaptic plasticity are known to be regulated by GABAergic inhibition, but how they are affected by changes in the GABA transporter activity remains unclear. Here we show that in the CA1 region of mouse hippocampus, pharmacological blockade or genetic deletion of GABA transporter-1 (GAT1) specifically impaired long-term potentiation (LTP) induced by theta burst stimulation, but had no effect on LTP induced by high-frequency stimulation or long-term depression induced by low-frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
63
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 51 publications
11
63
2
Order By: Relevance
“…Chronically elevated GABA levels also downregulated phasic GABA release and reduced presynaptic signaling via GABA B receptors, thus causing an enhanced tonic and a diminished phasic inhibition [36]. In a previous study using the same strain of GAT1 2/2 mice as used in our current research, Gong et al [18] demonstrated that GAT1 disruption specifically impaired TBS-induced LTP. They showed that GAT1 disruption specifically altered the temporal pattern of hippocampal theta oscillations by reducing the oscillation frequency, and these specific changes in the theta network activity and synaptic plasticity were accompanied by severe impairment of hippocampus-dependent learning and memory.…”
Section: Gat1supporting
confidence: 55%
See 3 more Smart Citations
“…Chronically elevated GABA levels also downregulated phasic GABA release and reduced presynaptic signaling via GABA B receptors, thus causing an enhanced tonic and a diminished phasic inhibition [36]. In a previous study using the same strain of GAT1 2/2 mice as used in our current research, Gong et al [18] demonstrated that GAT1 disruption specifically impaired TBS-induced LTP. They showed that GAT1 disruption specifically altered the temporal pattern of hippocampal theta oscillations by reducing the oscillation frequency, and these specific changes in the theta network activity and synaptic plasticity were accompanied by severe impairment of hippocampus-dependent learning and memory.…”
Section: Gat1supporting
confidence: 55%
“…However, mild changes were found in some genes involved in GABAergic and glutamatergic transmission, synaptic plasticity, and cognitive formation. Other evidences also indicated that neither genes expression nor synaptic structure changed significantly in the hippocampus of GAT1 knockout mice [18,36]. These data indicate that behavioral and electrophysiological changes in GAT1 ĂŸ/2 mice may mainly depend on the process of neurotransmision.…”
Section: Gat1mentioning
confidence: 83%
See 2 more Smart Citations
“…Dendritic spines were also vGLUT1 positive, indicating that spines were receptive to glutamatergic signaling. Interestingly, there were fewer vGLUT1-positive spines compared with synapsin1-positive spines, suggesting that some synapses may be involved in nonglutamatergic neurotransmitter pathways, which are also known to play an important role in learning and memory processing (Jerusalinsky et al, 1997;Gong et al, 2009). Fig.…”
Section: Discussionmentioning
confidence: 99%